Equity gap : Latin America, the Caribbean and the Social Summit (UN SantiagoCL, 1997)
Summarizes the situation in Latin America and the Caribbean in relation to the three main issues addressed at the World Summit - poverty, employment, social integration - within the wider context of economic change and social policy reform. Formulates proposals on these issues that will help in fulfilling the commitment undertaken in Copenhagen.
Bibliography: p. 201-210